The Cool Farm Biodiversity metric: An evidence-based online tool to report and improve management of biodiversity at farm scale - Crowther, Liam P.; Luke, Sarah H.; Arellano, Eduardo C.; McCormack, Caitlin G.; Ferreira, Vinina; Hillier, Jonathan; Heathcote, Richard; Kloen, Henk; Muñoz-Sáez, Andrés; Oliveira-Rebouças, Patricia; Oliveira da Silva, Fabiana; Rojas-Arévalo, Nadia; et al. (Ecological indicators, 2024)
Halting biodiversity loss and achieving food security are both aims of the United Nations 2030 Agenda for Sustainable Development, but there is complex interplay between them. Agriculture drives biodiversity loss, but biodiversity provides benefits to agriculture. There is substantial potential to develop ‘win-win’ solutions for biodiversity and people within productive farmland, by boosting wildlife that can be supported, whilst maintaining yield and other services. To achieve this, farmers need to be able to assess the impacts of their management on biodiversity at farm scale. While suitable tools exist to drive improvement in biodiversity management, none incorporates evidence on the effectiveness of specific management practices. In this study we present the Cool Farm Biodiversity metric, which generates a farm-scale action-based biodiversity management assessment, scored using expert judgements and expert assessment of experimental evidence. The metric is designed to be biome-specific, so it responds to conservation aims, ecosystem processes and farming systems in particular biomes. To demonstrate that the metric is responsive to changes in farm management, we present an example of use on a large arable farm from the temperate forest biome.